Government role and Tourism-related Micro and Small Businesses in the World Archaeological Heritage Site of Lenggong Valley Malaysia - Zulkefli, Nor Syuhada; Jaafar, Mastura; Rashid, Munira (2015)
Tourism and small businesses has been proven to have impact on economic development. Recognizing the important role played by SMEs in the nation’s economic activities, the government has introduced several programs and incentives to assist the tourism related SMEs. This study reviews the incentive and programs provided by government agencies for tourism related SMEs in Lenggong Valley. Lenggong, as a new UNESCO World Heritage Site in the state of Perak, Malaysia, provides vast opportunities for new businesses that are associated with micro and small businesses as the main contributor to enhance the economy in rural area. Thus, supervison by the government is essential for Lenggong Valley to excellently develop in tourism and economic sector. The study shown that most of the businesses were started by the middle age group with their own initiative, limited capital and less training. The study indicated that over half of the businesses had received government's support but the level of supportiveness was found explicitly low. Moreover, the study has discovered that many government agencies have been supporting the tourism related SMEs in Lenggong Valley. Among the government supports provided for the local businesses were capital, loan, course and training, marketing, consultancy, allocation and equipment supports. Amanah Ikhtiar Malaysa, MARA, TEKUN and Ministry of Tourism and Culture Malaysia, Perak are among the supportive government agencies. The government agencies assistance is crucial to ensure the tourism related SMEs maximise the advantages from tourism development.